A CONCEPTUAL REVIEW ON AGNIKARMA W S R THERAPEUTIC CAUTERIZATION - Aladakatti Shivakumara; J VAdithya; Aradhyamath Siddayya (International Journal of Applied Ayurved Research, 2021)
Ayurveda is the oldest and supreme science of medicine which deals about promotion of health and curing of diseases. Agnikarma is one among them which is explained under the context of Anushastra. Our Acharyas has explained about Agnikarma, its superiority, indications, contraindications and detailed description about Agnikarma Procedure. It is one of the methods of therapeutic Cauterization done using special tools at specific sites mentioned for specific diseases. Agnikarma is one of the procedures which relieve the pain very quickly. In this study a brief focus has been laid upon how this procedure helps in management of chronic diseases with pain as the chief presenting complaint. It has a special place in surgery because the disease will never reoccur if treated by this modality of treatment. In modern science, it is termed as Therapeutic Cauterization. This Review article helps us to understand about Agnikarma.